Autologous hematopoietic transplantation following COVID‐19 infection. Issue 3 (3rd January 2021) - Brzycki, Marthilde; Richard, Robert; Burwick, Nicholas; Graf, Solomon; O'Brien, Craig; Wu, Daniel; Chauncey, Thomas R.
Abstract: Autologous hematopoietic cell transplantation following induction therapy is standard of care for most patients with newly diagnosed multiple myeloma ( N Engl J Med 2017, 376 ; 1311). Though active COVID‐19 infection is typically a contraindication to aggressive therapy, little is known about the safety of autologous transplantation after resolution of acute symptoms and undetectable pathogen by nasopharyngeal PCR. Abstract : The majority of patients with underlying hematologic malignancy will survive acute COVID‐19 infection. For many, subsequent dose‐intensive therapy with autologous transplantation will be critical for optimal outcomes, and those with clinical recovery from COVID‐19 infection should not be precluded from consideration of autologous hematopoietic cell transplantation.